6000th Brilliant Problem Solved - Proof Problem

To commemorate my 6000th solved problem, which was this, I have decided to post this proof problem.

Let PP be a point inside equilateral triangle ABCABC. Let AA', BB' and CC' be the projections of PP onto sides BCBC, CACA and ABAB respectively. Prove that the sum of lengths of the inradii of triangles PACPAC', PBAPBA' and PCBPCB' equals the sum of lengths of the inradii of triangles PABPAB', PBCPBC' and PCAPCA'.

Note by Sharky Kesa
3 years, 6 months ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

Sort by:

Top Newest

Here's a proof, not very elegant though.

Let rΔXYZr_{\Delta XYZ} denote the inradius of ΔXYZ\Delta XYZ.

If ΔXYZ\Delta XYZ is right angled (XYZ=90\angle XYZ=90^\circ), then rΔXYZ=XY+YZZX2r_{\Delta XYZ}=\frac{XY+YZ-ZX}{2}

The proof of this is given as a note below.

Using this, we have the following equations:

rΔPAC=PC+ACPA2rΔPAB=PB+ABPA2rΔPBA=PA+BAPB2rΔPBC=PC+BCPB2rΔPCB=PB+CBPC2rΔPCA=PA+CAPC2\begin{aligned} r_{\Delta PAC'}&=\frac{PC'+AC'-PA}{2} \\r_{\Delta PAB'}&=\frac{PB'+AB'-PA}{2} \\r_{\Delta PBA'}&=\frac{PA'+BA'-PB}{2} \\r_{\Delta PBC'}&=\frac{PC'+BC'-PB}{2} \\r_{\Delta PCB'}&=\frac{PB'+CB'-PC}{2} \\r_{\Delta PCA'}&=\frac{PA'+CA'-PC}{2}\end{aligned}

The conclusion now follows.


Note:

If Δ\Delta denotes the area of ΔXYZ\Delta XYZ and ss denotes it's semi-perimeter, then rΔXYZ=Δsr_{\Delta XYZ}=\frac{\Delta}{s} Where XYZ=90\angle XYZ=90^\circ.

Now, we know that Δ=12XYZY\Delta = \dfrac{1}{2} \cdot XY \cdot ZY

So, rΔXYZ=XYZYXY+YZ+ZX    rΔXYZ=XYZY(XY+YZZX)(XY+YZ)2ZX2    rΔXYZ=XY+YZZX2\begin{aligned} r_{\Delta XYZ}&=\frac{XY \cdot ZY}{XY+YZ+ZX} \\\implies r_{\Delta XYZ}&=\frac{XY \cdot ZY \cdot (XY+YZ-ZX)}{(XY+YZ)^2-ZX^2} \\\implies r_{\Delta XYZ}&=\frac{XY+YZ-ZX}{2} \end{aligned}

The third implication follows by Pythagoras' Theorem.

The proof is now complete.

Also, notice that the fact that ΔABC\Delta ABC was equilateral was not required. The result holds for any arbitrary triangle ΔABC\Delta ABC.

Deeparaj Bhat - 3 years, 6 months ago

Log in to reply

@Sharky Kesa

Do you have an elegant proof?

Deeparaj Bhat - 3 years, 6 months ago

Log in to reply

No, this is my proof.

Sharky Kesa - 3 years, 6 months ago

Log in to reply

@Sharky Kesa Ok. Why the equilateral triangle though?

Deeparaj Bhat - 3 years, 6 months ago

Log in to reply

@Deeparaj Bhat I was hoping someone would have a proof specific for an equilateral triangle. Then, if it was asked for an arbitrary triangle, we could perform an affine transformation so it becomes an equilateral triangle, then use said proof.

Sharky Kesa - 3 years, 6 months ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...